(3GdGNJdGas - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG eG ENJUQg GdTjN CHh ESMGb Hf EHQGgje Hf Ydi GdTjQGRi ai ENJdGa GdTGaYi hGdMfai s
(3BNQgG (B:s
(3eSFdI GdcJGHI hGLHI bGd CHh MfjaI ZjQ hGLHI hGddg CYde JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3HgG HGSe YHO Gddg Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
Keywords: (3GdeLGejYs